Lessons learned in medical students’ remote social responsibility experiences during COVID-19 pandemic - Demirören, Meral; Atılgan, Bürge; Aslan, Dilek (Acta Medica, 2023)
Background: With the declaration of the COVID-19 pandemic in March 2020, face-to-face medical education was interrupted. To make first-year students a part of the fight against the pandemic, “We, as well, are in the Fight Against Novel Coronavirus Disease (COVID-19)!” remote social responsibility project was implemented in May 2020. Aim: The aim of the study was to evaluate the perceptions and opinions of medical students regarding their remote social responsibility experiences during the COVID-19 pandemic. Methods: Thematic content analysis of short-written reflection data collected to provide a deep insight into the experiences of the medical students was carried out. Results: The meaning and achievements of the remote social responsibility project revealed seven themes: “perception of social responsibility”, “perception of being medical students”, “perception of being a physician”, “fight against the pandemic”, “affective achievements”, “acquisition of generic skills” and “corporate commitment”. The findings draw attention to understanding the meaning of social responsibility, medical students’ and physicians’ role and responsibility in protecting health during the pandemic. Conclusion: Medical students providing social responsibility opportunities for their students during the pandemic enables them to be a part of the fight against the pandemic and ensure important gains. These gains also valuable in preparing them for pandemics and similar emergencies in their future professional lives. In addition, competencies such as communication in crisis environment, access to evidence-based information, informing the society that will prepare for crisis situations should be gained in the medical education.